The Importance of Character Education in School Bullying Cases - Yolanda Mutiara (Program Studi Pendidikan Islam Anak Usia Dini, Institut Agama Islam Ma'arif (IAIMNU) Metro Lampung, 2023)
Character education is an effort by educational institutions to prevent various educational problems, including bullying. Bullying is the act of using power to hurt someone or a group of people verbally, physically or psychologically, making the victim feel depressed, hurt and helpless. Adolescents who are victims of bullying have a higher risk of experiencing various health problems, both physical and mental. Problems that may be experienced by children who are victims of bullying include the emergence of various mental problems such as depression, anxiety, and sleep disorders that can persist into adulthood, as well as physical health problems such as headaches, abdominal pain, and muscle pain. stress, feelings of insecurity and safety in the school environment and reduced interest in learning and academic success. Therefore, character education must be improved so that similar cases do not recur. This study aims to identify the factors that contribute to the occurrence of bullying in adolescents, the role of bullying behaviour, and the types of bullying. The data source of this article was conducted using the descriptive analysis method. The article found that the factors that influence bullying behaviour can come from the individual's environment, family, playgroup, and the perpetrator's community. This action relates to the world of social work, in this case having to become a counsellor for the bully.